Development of a near infrared novel bioimaging agent via co-oligomerization of Congo red with aniline and o-phenylenediamine: experimental and theoretical studies. Issue 62 (13th November 2019) - Singh, Neetika; Kumar, Prabhat; Kumar, Raj; Aazam, Elham S.; Riaz, Ufana
Abstract : To study the effect of insertion of a multifunctional dye moiety on the photophysical properties of conducting polymers, the present paper reports for the first time the homopolymerization and co-oligomerization of Congo red (CR) dye with aniline and o -phenylenediamine. Abstract : With a view to study the effect of insertion of a multifunctional dye moiety on the photo physical properties of conducting polymers, the present paper reports for the first time the homopolymerization and co-oligomerization of Congo red (CR) dye with aniline and o -phenylenediamine. The co-oligomerization was established by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy ( 1 H-NMR), and ultraviolet-visible (UV-vis) spectroscopy while the morphology was examined using X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. The theoretical as well as experimental data of 1 H-NMR as well as IR studies confirmed the co-oligomer formation while ultraviolet-visible spectroscopy studies revealed a dynamic change in the optical properties upon variation of co-oligomer composition. X-ray diffraction studies established a crystalline morphology of oligomers. Live cell confocal imaging studies revealed that the co-oligomers could be effectively used in NIR imaging.